Excessive Neutrophil Extracellular Trap Formation Aggravates Acute Myocardial Infarction Injury in Apolipoprotein E Deficiency Mice via the ROS-Dependent Pathway. (21st May 2019) - Zhou, Zheliang; Zhang, Shuning; Ding, Suling; Abudupataer, Mieradilijiang; Zhang, Zhiwei; Zhu, Xiaowei; Zhang, Weiwei; Zou, Yunzeng; Yang, Xiangdong; Ge, Junbo; Hong, Tao
Abstract : Genetically human apolipoprotein E ( APOE ) ε 32 is associated with a decreased risk of ischemic heart disease. ApoE deficiency in mice impairs infarct healing after myocardial infarction (MI). After the ischemic injury, a large number of neutrophils are firstly recruited into the infarct zone and then degrade dead material and promote reparative phase transformation. The role of ApoE in inflammation response in the early stage of MI remains largely unclear. In this study, we investigated the effect of ApoE deficiency on neutrophils' function and myocardial injury after myocardial infarction. By left coronary artery ligation in ApoE -/- and wild-type (WT) mice, we observed increased infarct size and neutrophil infiltration in ApoE -/- mice. Within the infarct zone, more neutrophil extracellular traps (NETs) were observed in ApoE -/- mice, while increased ex vivo NET formation was detected in ApoE -/- mouse-derived neutrophils through the NADPH oxidase-ROS-dependent pathway. Suppressing overproduced NETs reduced myocardial injury in ApoE -/- mice after ligation. In general, our findings reveal a critical role of apolipoprotein E in regulating Ly6G + neutrophil activation and NET formation, resulting in limiting myocardial injury after myocardial infarction. In such a process, apolipoprotein E regulates NET formation via the ROS-MAPK-MSK1 pathway.